ICTs AND INCLUSION POLICIES IN BRAZIL: CONVERGING EFFORTS TOWARD MEMORY AND HERITAGE PRESERVATION - Nakano, Natalia [UNESP]; Vicentini Jorente, Maria Jose [UNESP]; Galindo, Marcos; Robinson, L.; Schulz, J.; Dunn, H. S. (Emerald Group Publishing Ltd, 2017)
Purpose - In Latin America, technology has been advancing faster than society is able to adjust to it on its own. Thus, information and communication professionals should merge their efforts to research and discuss the relevant role they play in the society transformed by technology. Methodology/approach - This paper presents and discusses the initiatives that the Brazilian government and stakeholder institutions are developing in regards to ICT and memory and heritage preservation. Findings - The international relevance of describing the Brazilian initiative of ruling the internet in a non-restrictive way shows the trend the country has adopted. Social implications - In the current context of development of the Information Society and expansion of cultural economy and digital culture in Brazil, it is imperative to define public policies for digitizing Brazilian memory and heritage collections. Such a national policy involving the three levels of the Federation as well as private institutions committed to the custody of cultural collections, should play an essential role in guiding the efforts to digital reproduction of collections and their publication on the internet. Originality/value - Brazil is the first country in the world to rule the use of internet openly, in a non-restrictive way, through the Marco Civil da Internet. Since 2007, an academic initiative named Memory Network has been working to promote the digitization and access to Brazilian collections of memory and heritage.
Keywords: Inclusion policies in Brazil; memory and heritage; Marco Civil da Internet; memory network